CuZnAlOOH catalysts with Cu0/Cu+ constructed by two-step hydrolysis for ethanol production from syngas. (15th August 2022) - Gu, Yinting; Han, Chun; Huang, Jinhua; Vinokurov, Vladimir A.; Huang, Wei
Graphical abstract: Highlights: adjustable Cu 0 /Cu + ratio was successfully constructed by two-step hydrolysis. Cu 0 /Cu + ratio can be adjusted by changing relative amount of CuZn gel/solution. Cu 0 /(Cu 0  + Cu + ) ratio has a good corresponding relationship with ethanol production. the catalyst morphology influences the production of by-products. Abstract: In this study, a CuZnAlOOH catalyst with adjustable Cu 0 /Cu + ratios is successfully prepared by two-step hydrolysis, affording two catalysts with different morphologies. By embedding Cu 0 grains on an oxide flake, a typical hydrogen spillover structure is formed, which is favorable for the hydrogenation of intermediates, with the production of a high number of hydrocarbons. On the other hand, by wrapping Cu 0 grains in an oxide, hydrogenation is inhibited, and γ-AlOOH and Cu/γ-AlOOH sites are exposed. Ethanol synthesis over the two sites is different from that over the active sites of Cu 0 grains embedded on a flake oxide. An approximate linear relationship exists between the mole ratio of CuZngel /(CuZnsolution  + CuZngel ) and that of surface Cu 0 /(Cu 0  + Cu + ). At CuZn gel/(solution + gel) ratios of 1/2–1/3, corresponding to the Cu 0 /(Cu 0  + Cu + ) ratios of 0.277–0.358, ethanol is produced in most advantage, the distribution of which is up to 55.5%.